Geography in early judaism and christianity : - Scott, James M. (Cambridge University Press, 2002)
James M. Scott focuses on a particular Old Testament pseudepigraphon--the Book of Jubilees. The book takes an interdisciplinary approach based on detailed analysis of primary sources, much of which is seldom considered by New Testament scholars, and explores the neglected topic of ancient geographical conceptions. By studying geographical aspects of the work, Dr Scott is able to relate Jubilees to both Old and New Testament traditions, bringing important new insights into Christian concepts of annunciation.